A small step towards the citizen sensor: A multi-purpose framework for mobile apps - Galeazzo, Daniel Aurelio; De Vecchi, Daniele; Dell'Acqua, Fabio; Demattei, Pietro (2015 IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2015)
The concept of crowdsourcing is to collect and share information from "the crowd". The diffusion of smartphones and tablets led to what can be pictured as a "dense network of observers" that can be used to submit useful data possibly complementing satellite-based Earth observation. In this paper, we propose a multi-purpose framework specifically designed to collect data in a distributed way; the model is based on a client-server architecture and an open-source framework including PHP and SQL. Communication among the devices is guaranteed by standard protocols like HTTP and JSON. An example of application based on this framework is also presented; the main objective is to collect information about water quality by asking users to provide feedback. The interface is both web- and mobile-based.